1999
DOI: 10.1152/ajpregu.1999.276.5.r1506
|View full text |Cite
|
Sign up to set email alerts
|

Heat acclimation increases the basal HSP72 level and alters its production dynamics during heat stress

Abstract: It has been previously shown that heat acclimation leads to an elevated basal level of 72-kDa heat shock protein (HSP72). Augmented expression of HSP72 is considered as a cytoprotective response. This led us to hypothesize that alterations in the heat shock protein (HSP) defense pathway are an integral part of the heat acclimation repertoire. To investigate this, we studied the temporal profile of basal HSP expression upon acclimation and the dynamics of their accumulation subsequent to acute heat stress (HS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
167
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(191 citation statements)
references
References 28 publications
21
167
0
3
Order By: Relevance
“…In addition, variation in Hsp70 gene expression and polymorphisms has been positively correlated with variation in thermotolerance in Drosophila melanogaster, in Caenorhabditis elegans, in rodents and in humans (Hashmi et al, 1997;Maloyan et al, 1999;Sonna et al, 2002;Gong and Golic, 2004;Singh et al, 2006). In farm animals, some studies reported possible associations of SNP in the Hsp70 genes with stress response and tolerance to heat.…”
Section: Hsp70 Genotype and Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, variation in Hsp70 gene expression and polymorphisms has been positively correlated with variation in thermotolerance in Drosophila melanogaster, in Caenorhabditis elegans, in rodents and in humans (Hashmi et al, 1997;Maloyan et al, 1999;Sonna et al, 2002;Gong and Golic, 2004;Singh et al, 2006). In farm animals, some studies reported possible associations of SNP in the Hsp70 genes with stress response and tolerance to heat.…”
Section: Hsp70 Genotype and Heat Stressmentioning
confidence: 99%
“…LTHA is characterized by a reprogrammed gene expression and cellular response resulting in enhanced efficiency of signalling pathways and metabolic processes (Horowitz, 2002), and this, in large part, may be mediated by heat shock proteins (Hsp; described later; Maloyan et al, 1999). This phase of acclimation is also characterized by endocrine changes and this is presumably with the goal of decreasing metabolic heat production and increasing heat dissipation.…”
mentioning
confidence: 99%
“…The expression profiles of HSP have been shown elsewhere to return to basal levels within hours of a stress event (Collier et al 2006), although acclimation would deem that these animals, after 120 days in the feedlot, had acclimatised to their thermal environment. In rats however, acclimated animals had an increased concentration of HSP70 mRNA compared with nonacclimated animals (Maloyan et al 1999). This was further demonstrated by Horowitz (2002), who showed that long-term acclimated rats have drastically increased HSP70 mRNA, although this is in the heart and brain tissue.…”
Section: Discussionmentioning
confidence: 83%
“…In fact, in addition to the rapid heat shock response, chronic exposure to moderate heat may induce HSP accumulation, and since HSPs overexpression in cultured cells elevate the degree of the lethal temperature, their accumulation on long-term heat acclimatization could also contribute to the elevation of the upper body core temperature safety margin and reduce heat illness risk. 20,[37][38][39] In this respect, comparisons of Hsp70 levels between organisms inhabiting either normothermic or hot environments showed that the hot-environment species have higher HSP levels compared with species of the same genus inhabiting normothermic environments. 20 Hsp72 overexpression in multiple vital organs including the heart and the brain has been demonstrated to confer protection against heatstrokeinduced hyperthermia, circulatory shock, and cerebral ischemic injury in rats and mice.…”
Section: Role Of Hsps In Heat Adaptation and Protection Against Heatsmentioning
confidence: 99%